Vascular progenitor clusters from peripheral blood in cancer patients following oncologic surgery. Issue 2 (21st October 2013) - Javidnia, Hedyeh; Hanna, Mary; Li, Yuhua; Scheer, Adena; Filion, Lionel; Eapen, Libni; Carrier, Marc; Auer, Rebecca; Corsten, Martin; Allan, David S.
Abstract Introduction Vascular progenitor cells (VPCs) are recruited into the peripheral blood (PB) following ischemia and inflammation and correlate with vascular health. The impact of recruiting VPCs on surgical recovery and cancer progression following tumor resection remain unknown. Methods We measured VPC clusters and enumerated circulating CD34+ VEGFR2+ angiogenic cells in 18 patients with oral cancer (OC) undergoing resection and free flap reconstruction (high vascular injury) and in 18 patients undergoing colorectal cancer resection (CRC) (low vascular injury) at baseline and multiple timepoints after surgery. Results VPC clusters increased following OC resection, peaking on Day +3 and returning to baseline by Day 28. In contrast, VPC clusters decreased sharply on Day +3 in patients with CRC before returning to baseline. CD34+ VEGFR2+ cells did not increase significantly after surgery. More rapid clinical recovery following OC resection was observed in patients with greater VPC cluster levels on Day +3. Tumor size and subsequent progression of cancer did not correlate with recruitment of VPC cluster‐forming cells. Conclusion VPC recruitment following cancer resection may depend on cancer subtype and may relate to the degree of surgical stress and vascular injury. Recovery after surgery for OC may be accelerated in patients with greater VPC recruitment. J. Surg. Oncol. 2014 109:151–157. © 2013 Wiley Periodicals, Inc.